Registry study of immune-related adverse events using electronic patient-reported outcome in patients with cancer receiving immune checkpoint inhibitors: protocol for a multicentre cohort study - Takuhiro Yamaguchi; Tempei Miyaji; Takashi Kawaguchi; Kanako Azuma; Taiki Hirata; Ayako Torii; Hiroaki Usui; Soan Kim; Tatsuya Hayama; Daisuke Hirate; Yosuke Kawahara; Yuki Kumihashi; et al. (BMJ Open)
Introduction The use of immune checkpoint inhibitors (ICIs) is rapidly expanding in cancer treatment. ICIs have a unique safety profile, characterised by immune-related adverse events (irAEs). The safety profile of ICIs lacks patient experience and perspectives. This study primarily aims to obtain a database for descriptive research on the status of irAEs using the Patient-Reported Outcomes version of the Common Terminology Criteria (PRO-CTCAE) in patients with gastrointestinal cancer, lung cancer and malignant pleural mesothelioma treated with regimens containing ICIs.Methods and analysis This is an ongoing, multicentre, observational study in Japan. Eligible patients must be at least 20 years old and have been diagnosed with lung cancer, malignant pleural mesothelioma or gastrointestinal cancer and plan to use ICIs. Participants will install the electronic PRO (ePRO) application and report adverse events via ePRO using PRO-CTCAE once weekly for up to 48 weeks. A registry will be established using background information obtained from medical records. The sample size is determined by 1 year projection without using statistical methods. Statistical analyses will include point estimates and 95% CIs for the incidence of each adverse event by cancer type and regimen at each time point.Ethics and dissemination This research will be conducted per the Declaration of Helsinki, the Ethical Guidelines for Life Science and Medical Research Involving Human Subjects issued by the Ministry of Education, Culture, Sports, Science and Technology and the Ministry of Health, Labor and Welfare, and the revised Personal Information Protection Law. The study protocol was approved by the Ethics Committee (approval ID T2021-0180) of Tokyo Medical University Hospital on 15 October 2021.Registration details The study began enrolling patients in December 2021. The target enrolment is 260; as of October 2022, 141 have been enrolled, and the enrolment is scheduled to end on 30 June 2023.Trial registration number UMIN000046418